2010
DOI: 10.1002/ajh.21772
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of hydroxyurea in reducing the frequency of pain episodes and hospitalization in pediatric sickle cell disease

Abstract: In a cohort of children with sickle cell disease (SCD) and vaso-occlusive pain visits served through South Carolina's Medicaid system over a 6-year period (N 5 523), we compared the number of vaso-occlusive pain or acute chest syndrome (ACS)/pneumonia episodes, and outpatient or acute service costs in those treated or not treated with hydroxyurea (HU). HU may be an underused intervention for SCD in this practice setting, for a variety of reasons. Treatment with HU varied greatly, appears to have been administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 160 publications
4
34
0
Order By: Relevance
“…Physicians appear to prescribe HC primarily to SCD patients with high vaso-occulsive severity, as epidemiological studies show an association of HC use with more frequent hospitalizations (Lanzkron et al, 2006;Stallworth et al, 2010). Our results suggest that the same was true in the patient sample we analysed.…”
Section: Discussionsupporting
confidence: 55%
“…Physicians appear to prescribe HC primarily to SCD patients with high vaso-occulsive severity, as epidemiological studies show an association of HC use with more frequent hospitalizations (Lanzkron et al, 2006;Stallworth et al, 2010). Our results suggest that the same was true in the patient sample we analysed.…”
Section: Discussionsupporting
confidence: 55%
“…Ourfindings are consistent with previous findings. Under usual-care conditions, 2-3 years of HU use is safe and effective in children and adolescents [27].…”
Section: Discussionmentioning
confidence: 99%
“…Another study examined the cost and effectiveness of hydroxyurea in reducing the frequency of pain episodes and hospitalization in pediatric sickle cell disease in South Carolina. 12 Analysis of that state's Medicaid records indicated that those receiving the drug had a higher risk of experiencing vaso-occlusive pain episodes and ACS, as well as significantly higher medical costs than those children not receiving hydroxyurea, which was attributed to the hydroxyurea users having greater severity of disease. However, among those receiving hydroxyurea, average costs fell 31% from $12 842 to $8839 (P , .001) during the 2-3 year period of active treatment.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Although the MarketScan database does not identify the 12 states contributing data, those data may be more generalizable at the national level than cost estimates from individual states used in previous cost studies. 11,12,20 Of note, the claims data used to estimate hospitalization costs lacked sociodemographic information except for age (which was controlled in this analysis by restriction to 1-to 3-yearold children), gender, and, to a limited extent, race/ethnicity. 14 Another limitation of those data are the use of ICD-9 billing codes to identify children with sickle cell anemia; previous analyses of these data have found that the overall frequency of sickle cell disease among children reported to be black or African American is accurate but that information on subtypes of sickle cell disease is often lacking or imprecisely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation